ENERGY OF NON-COPRIME GRAPH ON MODULO GROUP - Karang, Gusti Yogananda; Wisnu Wardhana, I Gede Adhitya; Angamuthu, Manimaran (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
A graph is a mathematical structure consisting of a non-empty set of vertices and a set of edges connecting these vertices. In recent years, extensive research on graphs has been conducted, with one of the intriguing topics being the representation of graphs within algebraic structures, particularly groups. This approach bridges two areas of mathematics: graph theory and algebra. This study focuses on graph representation, specifically non-coprime graphs in the group of integers modulo ​, where , is a prime number, and is a non-negative integer. The non-coprime graph of a group is defined as a graph with the vertex set , where is the identity element of . Two distinct vertices and are connected by an edge if . Specifically, this research investigates the Sombor energy, the Degree Sum energy, the Degree Exponent Sum energy, the Laplacian energy, the Distance Laplacian energy, and the Distance Signless Laplacian energy of a non-coprime graph on a modulo group.